1994
DOI: 10.1002/jnr.490380113
|View full text |Cite
|
Sign up to set email alerts
|

Delayed application of aurintricarboxylic acid reduces glutamate‐induced cortical neuronal injury

Abstract: The non-specific endonuclease inhibitor, aurintricarboxylic acid (ATA), attenuated glutamate-induced destruction of cultured cortical neurons. In part, this protective effect likely reflected the ability of ATA to produce a slowly developing block of N-methyl-D-aspartate receptor-mediated inward whole cell current or increase in intracellular free Ca2+. However, ATA also attenuated a high K(+)-induced increase in intracellular free Ca2+ in the presence of D-amino-phosphonovalerate, suggesting that ATA may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…There has been a long-standing, primarily implicit assumption that such trauma-induced spinal cord cell death, like the death of brain cells induced by several acute insults, represents the form of death called "necrosis" (Kerr et al, 1972;Balentine, 1978a,b;Selina et al, 1989). This assumption is consistent with the more recent implication of excitotoxicity in the pathogenesis of traumatic spinal cord damage (Faden and Simon, 1988;Panter et al, 1990;Wrathall et al, 1992), because excitotoxicity is typically marked by early neuronal cell swelling (Coyle et al, 1981) and likely leads preferentially to necrosis (Csernansky et al, 1994;G wag et al, 1996).…”
supporting
confidence: 79%
“…There has been a long-standing, primarily implicit assumption that such trauma-induced spinal cord cell death, like the death of brain cells induced by several acute insults, represents the form of death called "necrosis" (Kerr et al, 1972;Balentine, 1978a,b;Selina et al, 1989). This assumption is consistent with the more recent implication of excitotoxicity in the pathogenesis of traumatic spinal cord damage (Faden and Simon, 1988;Panter et al, 1990;Wrathall et al, 1992), because excitotoxicity is typically marked by early neuronal cell swelling (Coyle et al, 1981) and likely leads preferentially to necrosis (Csernansky et al, 1994;G wag et al, 1996).…”
supporting
confidence: 79%
“…NMDAR-mediated neurotoxicity is strictly associated with the increase in cytosolic calcium level ([Ca 2? ] c ) [36,37] and enhanced ROS production [38]. Interestingly, in the present study, the staurosporine-induced enhancement in [Ca 2? ]…”
Section: Discussionmentioning
confidence: 65%
“…However, later studies showed that this could be attributable to decreased glutathione instead of the conventional receptor-mediated toxicity (Murphy et al, 1989;Ratan et al, 1994). Other reports argue against an apoptotic mechanism (Dessi et al, 1993;Csernansky et al, 1994). Making the issue more complicated are reports that glutamate-induced cell death could be either apoptotic or necrotic depending on the intensity of stimuli or the ability of neurons to recover mitochondrial membrane potential .…”
Section: Discussionmentioning
confidence: 99%